Integrating Scientific Approaches into Adobe Animate- Assisted Interactive Media: Enhancing Geometric Spatial Skills for Secondary Education - Ani Afifah; N. Zumro (Universitas Muhammadiyah Malang, 2026)
This study aims to develop interactive learning media based on Adobe Animate integrated with a scientific approach, specifically focusing on flat-sided solid shapes such as cubes and cuboids. Employing the ADDIE development model—comprising Analysis, Design, Development, Implementation, and Evaluation—the research involved 32 eighth-grade students at MTsN 6 Pasuruan. The results indicate that the developed media fulfills high standards of quality, categorized as